(3Gdbhi GdWHjYjIs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS (B: (3Efg deG cGf GdMS hGdMQcI GdEOGQjI NGUjf HGdMjhGf , hGdfehQ hGdJZPi YGejf ddMjhGf hGdfHGJ s
(3BNQgG (B:s
(3aEPG cGf ai CaVjI GdYQhb GdVhGQH HNGQ hghGA hOe dWja, de JLJPH ef GdCNdGW GdeMJSHI ai GdeYOI hGdCeYGA TjFkG CUdG, Ch cGf eG JLJPHg TjFkG jSjQkG LOkG s
(3fSNI KGfjIs
(3hgh ai KdGK ebGdGJs
(3hZQVI ajg Cf jHjf Cf JOHjQ GdHOf jchf HKdGK bhi WHjYjIs
(3hgj GdbhI GdLGHdI hGdbhI GdefejI s
(3hGdbhI GdZGPjI s
(3hgh GdcJGH GdSGHY ef LhGeY GdEScfOQGfjjf s
Keywords: (3GdWHs